Microwave-assisted cassava pulp hydrolysis as food waste biorefinery for biodegradable polyhydroxybutyrate production - Prasertsilp, Patiya; Pattaragulwanit, Kobchai; Kim, Beom Soo; Napathorn, Suchada Chanprateep (Frontiers in Bioengineering and Biotechnology, 2023)
Cassava pulp is one of the most abundant agricultural residues that can cause serious disposal problems. This study aimed to apply a biorefinery approach by examining the feasibility of microwave-assisted cassava pulp hydrolysis to attain sustainable management and efficient use of natural resources. Four factors, namely, the liquid-to-solid ratio (20, 10, 7.5 and 5 mL/g), types of acids (H2SO4 and H3PO4), watt power (600, 700 and 800 W) and time (3, 5 and 8 min), were carefully investigated. The highest fermentable sugar content of 88.1 ± 0.7 g/L (0.88 g fermentable sugars/g dry cassava pulp) was achieved when 20 mL/g cassava pulp was hydrolyzed with 2.5% (v/v) H2SO4 under microwave irradiation at 800 W for 8 min. Glucose was a major product (82.0±5.2 g/L). The inhibitor concentration was 5.17 ± 0.01 g/L, and the levulinic acid concentration was 5.15 ± 0.01 g/L. The results indicated that the liquid-to-solid ratio, diluted acid concentration, irradiation watt power and time were important factors in producing fermentable sugars from acid hydrolysis under microwave irradiation. The crude hydrolysate was used for PHB production by Cupriavidus necator strain A-04. The hydrolysate to nutrients ratio of 30:70 (v/v) yielded a cell dry weight of 7.5 ± 0.1 g/L containing PHB content of 66.8 ± 0.3% (w/w), resulting in a yield (g-PHB/g- ) of 0.35 g/g. This study demonstrated that the microwave-assisted cassava pulp hydrolysate developed in this study provided a high amount of glucose (88.1% conversion) and resulted in a low concentration of inhibitors without xylose; this was successfully achieved without pregelatinization, alkaline pretreatment or detoxification.